Conceptual model of unit trust waqf based on fixed unit trusts structure - Sulaiman, Syahnaz; Kamaruddin, Muhammad iqmal hisham; Johari, Fuadah; Hasan, Aznan (Academy of Contemporary Islamic Studies (ACIS), 2020)
This paper aims to present the viability of unit trust waqf as an alternative asset class for waqf creation. The paper provides the conceptual framework of unit trust waqf based on the existing fixed unit trusts structure managed under Permodalan Nasional Berhad (PNB). This paper starts with the conceptual exploration of the literature in the area of waqf, which are sourced from authentic sources of al-Quran and al-Hadith, as well as secondary sources such as books, journal articles and online resources. The novelty of this paper lies in its attempt to highlight the importance of waqf investment strategy in ensuring the perpetuity of waqf by preserving its capital to maintain sustainable return for waqf beneficiaries. PNB’s fixed unit trust structure has been identified as a viable conceptual model for unit trust waqf to pool more cash waqf from individual investors. The sustainability of the capital waqf assets in the form of unit trust is preserved through the parameters for its application as proposed toward the end of the paper.